POLEMIK HADIS ISBAL - Ahmad Syifa; Awalia Rohmah (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2020)
This article aims to understand the isbāl contained in the hadiths of the Prophet and give birth to the phenomenon of dress itself among the people. Thus, the focus is on how the hadiths of the Prophet provide information about isbāl and its meaning. In addition, bangaimana responds to phenomena that occur in the community. The description of this article shows that Isbāl is the behavior of lengthening clothing beyond the ankles. The isbāl controversy was born because of the existence of substantive contradictory hadiths of the Prophet. The hadith that advocates and forbids gives birth to differences in views and meanings of isbāl itself. Therefore, the understanding of Isbāl hadith must use the approach of contradictory hadiths which in Islamic treasures is referred to as the science of mukhtalif al-ḥadīṡ. Sociologically-anthropologically, claim-truth is a fundamental factor in the controversy over the practice of dressing with isbāl.